Analyzing Disney Mulan’s Hero’s Journey in Terms of Literature (Lembaga Pengembangan Kinerja Dosen, 2025)
This study analyzes the reinvention of heroism and gender identity in Disney's Mulan (1998), an animated adaptation of the Chinese mythology of Hua Mulan. Mulan diverges from conventional storylines that exalt masculine power and martial prowess, focusing instead on themes of heroism, self-discovery, and the subversion of strict gender standards. The film amplifies a female protagonist who defies cultural norms, critiquing traditional heroics and redefining greatness via resilience, intellect, and ethical purity. This study utilizes qualitative textual analysis and Joseph Campbell’s Hero’s Journey framework to examine how Mulan subverts patriarchal tropes, establishing personal sincerity and inner power as the genuine criteria of heroism. This study examines feminist and postcolonial critiques of classical storytelling, asserting that Mulan reinterprets old myth as a modern metaphor of empowerment, demonstrating how contemporary adaptations can reclaim traditional narratives to embody progressive ideas. The video serves as a radical act of mythopoetic resistance, presenting an alternative conception of heroism that surpasses gender and cultural limitations.